Economic Effects of Brexit on the European Economy - Gabriel Felbermayr; Clemens Fuest; Jasmin Katrin Gröschl; Daniel Stöhlker (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2017)
On 29 March 2017, the UK Government notified its exit to the EU in accordance with Article 50 of the EU Treaty. Brexit is therefore officially initiated. On 29 April, the Heads of State and Government of the European Council adopted the guidelines for negotiations between the EU and the UK in accordance with Article 50 TEU. Negotiations between the EU27 and the UK on the important issues of exit and discussions on future political and economic relations between the EU27 and the UK have begun in July 2017 and have proven difficult since then. Of course, the two stage structure suggested by the EU makes an agreement difficult precisely because the appropriate side payments will depend on the agreement about future economic relations. In this note, Clemens Fuest, Gabriel Felbermayr, Jasmin Groeschl and Daniel Stöhlker wish to provide some empirical foundations for the political process. First, they characterize the value chains that tie the UK and the EU together. Second, they identify how the different goods and services sectors have benefitted from the UK's membership in the EU Single Market and Customs Union. These benefits – on both the UK and the EU side – are now at risk due to Brexit. Third, they simulate different scenarios, utilizing the ifo trade model, to quantify the consequences of Brexit for the UK and EU countries. The study uses increasingly complex models to meet the above objectives.
Keywords: 330